Morphological Characteristics of Molybdenum Disulfide and Current Application on Detecting SF6 Decomposing Products - Qian, Guochao; Peng, Qingjun; Wang, Haozhou; Wang, Shan; Dai, Weiju (Frontiers in Materials, 2020)
MoS2 has been considered a potential novel material in various fields due to thelarge specific surface area, high carrier mobility and tunable electronic properties. However, with the increasing demand for substrate properties, different strategies have been made to achieve its high performances, usually by adopting the method of controling microstructure. SF6 gas-insulated electrical equipment has gained considerable attention in electric system with the advantages of small volume, high security, strong breaking performance and fracture tolerance high-pressure. Nevertheless, in the process of equipment operation, the SF6 gas will occur inevitably decomposition due to partial discharge, resulting in the deterioration of insulation performance of the equipment. Therefore, detecting SF6 decomposition products is of positive significance for the safe and stable operation of power system. In this mini-review, we start from the synthesis of various MoS2 morphological structures. Then, the beneficial characteristics of the unique synthesized nanostructures at present are analyzed. Besides, we focus on the gas-sensing mechanisms and applications of the MoS2 based sensors for detecting SF6 decomposition products. Finally, the future development in this field is proposed.